2021
DOI: 10.4081/jphr.2021.2157
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Team Communication in Hospitals: A Quasi-Experimental Study using a Modified Teamstepps

Abstract: Background: Communication is a bridge of transaction between the health team, patients, and families that applies in the service units of hospitals, which are closely related to the patient safety culture. TeamSTEPPS is a team strategies and tools to enhance performance and patient safety. Therefore, this study aims to analyze the effect of modified TeamSTEPPS training on the team communication of nurses in hospitals.Design and Methods: This study used a quasi-experimental pre-posttest control group design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, contrasting findings were represented by Kwon and Duzyj who reported no substantial changes in perceptions of team dynamics or behaviors to promote patient safety among the physician and nurses at the regional perinatal center after teamwork training [37]. Similarly, the study conducted by Ahsan et al found no noteworthy differences in attitudes and perceptions toward team communication between intervention and control groups [38]. Discrepancies in these results might be linked to differing sample sizes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, contrasting findings were represented by Kwon and Duzyj who reported no substantial changes in perceptions of team dynamics or behaviors to promote patient safety among the physician and nurses at the regional perinatal center after teamwork training [37]. Similarly, the study conducted by Ahsan et al found no noteworthy differences in attitudes and perceptions toward team communication between intervention and control groups [38]. Discrepancies in these results might be linked to differing sample sizes.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, Kwon and Duzyj collected the data from 20 physicians and 15 nurses before training and from 9 physicians and 20 nurses 6 months post-training [37]. However, the study by Ahsan et al involved 28 nurses in control and intervention groups [38]. The dissimilarities in sample sizes might influence the sensitivity of detecting changes in perceptions, potentially explaining the divergent findings between these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, 101 medication errors occur per 1,000 drug prescription cases ( 9 ) , and it is also estimated that drug errors cause 12,000 deaths per year according to the National Health Service (NHS) ( 10 ) . The number of reported events increased from 135,356 between October and December 2005 to 508,409 during the same period in 2017 ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, nurses and patients' families communicate closely, therefore, they can easily identify the physical, psychological, and social problems faced by patients and their families. 18,19 In summary, nurses play crucial roles in establishing professional PC teams. 20 Thus, assessing the quality of PCs provided by nurses is critical to improving the quality of patient care.…”
Section: Introductionmentioning
confidence: 99%